The impact of supervisor–worker relationship on workers’ safety violations: a modified theory of planned behaviour - Su, Yikun; Cong, Weiyi; Liang, Huakang (Journal of Civil Engineering and Management, 2019)
This study develops and tests an integrative model to better understand the mechanisms by which the leadermember exchange (LMX) determines workers’ safety behaviours. The modified theory of planned behaviour (TPB) was proposed by using attitudinal ambivalence to replace univalent safety attitude. Empirical data were collected from 229 construction workers in China using a detailed questionnaire. Both situational and routine safety violations were considered in this model. The results showed that LMX had significant effects on both types of safety violations through three mediators from the modified TPB framework. Specifically, attitudinal ambivalence and group safety norm mediated the relationships between LMX and both types workers’ safety violations. However, perceived behavioural control only mediated the relationship between LMX and individuals’ routine safety violations. Furthermore, this research supported the distinctions between situational and routine safety violations. The indirect effects of LMX on individuals’ situational safety violations took place mainly through group safety norm. By contrast, the indirect effects on individuals’ routine safety violations took place mainly through attitudinal ambivalence and perceived behavioural control. Finally, the theoretical and practical implications, research limitations, and future directions were discussed. The results provide some meaningful insights into how to improve safety compliance behaviours from the perspective of supervisor-worker relationships.